2023
DOI: 10.22540/jfsf-08-023
|View full text |Cite
|
Sign up to set email alerts
|

Balance performance and grip strength as predictors of cognitive function among community-dwelling older adults in the USA

Abstract: Objectives: To investigate how balance and grip strength predicts the probability of cognitive function impairment (i.e., executive function: mild and mild-to-moderate impairment, and delayed recall) over eight years in community-dwelling older adults in the US, controlling for sex and race/ethnicity. Methods: The National Health and Aging Trends Study dataset (2011 – 2018) was employed. Dependent variables included the Clock Drawing Test (Executive Function) and Delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The results showed that individuals with dynapenia had a high risk of cognitive decline. While the link between muscle weakness and cognitive decline has been reported in previous studies, 38–42 this study demonstrated an association even among individuals with maintained muscle mass using a large‐scale sample from multiple cohorts.…”
Section: Discussionmentioning
confidence: 42%
“…The results showed that individuals with dynapenia had a high risk of cognitive decline. While the link between muscle weakness and cognitive decline has been reported in previous studies, 38–42 this study demonstrated an association even among individuals with maintained muscle mass using a large‐scale sample from multiple cohorts.…”
Section: Discussionmentioning
confidence: 42%